2015
DOI: 10.1177/1363460714550904
|View full text |Cite
|
Sign up to set email alerts
|

‘A world turned upside down’: Emotional labour and the professional dominatrix

Abstract: The professional dominatrix, who has been underrepresented in the literature on sex work, complicates our understanding of the emotional labour of sex work. The professional dominatrix is paid by clients to perform the role of the dominant in scenarios involving bondage, discipline, dominance, submission, sadomasochism, and 'fetishism.' Unlike other sex workers, who must often feign interest and act flirtatiously in order to make clients feel desired, the dominatrix is asked, at times, to express emotional dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Khan (2009) analyzed representations of dominatrices in film and criminal trials, and found consistent emphases on women’s gender transgression. In an investigation of emotional labor in the field, Pinsky and Levey (2015) found that dominatrices were expected to demonstrate feminine-coded traits, such as compassion and shy flirtation, as well as masculine-coded traits, such as aggression and detachment. McClintock depicted the dungeon as a “house of misrule” where “woman is judge and jury [and] man is penitent” (1993: 106).…”
Section: Prior Research On Professional Bdsmmentioning
confidence: 99%
See 3 more Smart Citations
“…Khan (2009) analyzed representations of dominatrices in film and criminal trials, and found consistent emphases on women’s gender transgression. In an investigation of emotional labor in the field, Pinsky and Levey (2015) found that dominatrices were expected to demonstrate feminine-coded traits, such as compassion and shy flirtation, as well as masculine-coded traits, such as aggression and detachment. McClintock depicted the dungeon as a “house of misrule” where “woman is judge and jury [and] man is penitent” (1993: 106).…”
Section: Prior Research On Professional Bdsmmentioning
confidence: 99%
“…Two gaps in the literature are particularly important for this article. First, scholars have overwhelmingly focused on cisgender women professionals (Khan, 2009; McClintock, 1993; Pinsky and Levey, 2015). Wilson (2005) explicitly defined “dominatrix” as “a woman who, normally for financial purposes, participates in forms of sexually charged role-play with a fetishistic or sadomasochistic backdrop” (2005: 32).…”
Section: Prior Research On Professional Bdsmmentioning
confidence: 99%
See 2 more Smart Citations
“…The journal has showcased seldom aired research on BDSM (Lindemann, 2011) and professional dominatrix work (Pinsky and Levey, 2015), transgendered identities (Ocha and Earth, 2013) as well as men who have sex with men in a commercial context (Atkins and Laing, 2012;Hall, 2007;Smith, 2012).…”
Section: Diversity In Sex Workmentioning
confidence: 99%